Pengaruh Pelatihan Penilaian Praktik Seni Budaya Berbasis Pergelaran bagi Guru Seni Budaya SMK di Salatiga - Widhiardanti, Rosalia Meita; Iriani, Ade; Hadi, Wasito (Resital: Jurnal Seni Pertunjukan, 2022)
Art education is one of the major determinants in improving the skills of 21st century students. Various assessment in art education is held to create active and creative students, one of them is the performance-based arts and culture assessment. The limited ability of teachers and the lack of learning resources for teachers so that the implementation in several schools has not been implemented and is not running effectively and efficiently, so teachers need reinforcement in the form of training. This study aims to see the effect of performance-based cultural arts practice assessments training for arts and culture teachers. The training was carried out in a limited with a small sample of 5 art and culture teachers from SMKN 1, SMKN 2, SMKN 3, SMK Bhakti Nusantara Salatiga.  The research used quantitative research with a pre-experimental of One Group Pretest Posttest Design with data collection techniques in the form of interviews, documentation studies and tests. Interviews and documentation studies were conducted to analyze the needs of the training carried out. The test used to measure the teacher's understanding and knowledge of material by giving a pretest and posttest. The data analysis technique was processed by quantitative descriptive techniques by conducting the Normality Test and the Paired Samples T-Test. The results showed that the value of sig. (2-tailed) is 0.012 (< 0.050), meaning that H0 is rejected and Ha is accepted. Therefore, it can be said that there is an increase in competence between before and after the training is carried out.